APPLICATION OF ACCRUAL PRINCIPLE FOR THE PURPOSE OF LEGAL ENTITIES TAXATION ON CORPORATE INCOME TAX - Endrijaitis, Martynas (Teisė, 2015)
Foreign scientists recently have given more attention to problematic questions of corporate income tax connection with legal regulation of financial accounting, and have also emphasized financial accounting importance to tax law. However, despite the fact that there are some publications which assess transactions for financial accounting and taxation purposes in practical view in special press, there is not any scientific research on corporate income tax connection with financial accounting in Republic of Lithuania. In addition, scientists of Republic of Lithuania analysis the accrual principle and only define and describe this principle in financial accounting. Consequently, application of the terms by which income and costs are recognized for the purpose to calculate corporate income tax base has not been analyzed. This article aims to define the basic statement on taxation “income is recorded when earned and costs – when they occur”, and to show how the accrual principle should be applied by legal entities to pay corporate income tax. Analysis is based on the systemic review of the Law on Corporate Income Tax, Business accounting standards framed by The Authority of Audit and Accounting, scientific literature and Tax dispute settlement institutions case-law. With reference to the purpose of this article, there are defined the terms which are necessary for recognision income and costs for taxation purpose. The article disclose that for taxable income recognision using the accrual principle must be followed these conditions: 1) the selling entity has transferred to the buyer the risks and rewards of ownership of the goods; 2) it is probable that the economic benefits associated with the transaction will flow to the entity and the amount of revenue can be measured reliably; 3) the costs related to the sale transaction can be measured reliably. Consequently, costs recognision terms for taxation purpose are: 1) only that portion of expenses of the previous and reporting periods that is related to the income earned during the reporting period is recognised as costs; 2) the costs related to the sale transaction can be measured reliably. In addition to this, there is a special term for the appropriate executing of tax burden – to answer the question whether Law on Corporate Income Tax does not provide otherwise? This scientific research reveals substance and application of accrual principle on taxation with corporate income tax aiming to prove importance of financial accounting norms to assessing corporate income tax base.